2015
DOI: 10.1530/joe-15-0121
|View full text |Cite
|
Sign up to set email alerts
|

60 YEARS OF NEUROENDOCRINOLOGY: Redefining neuroendocrinology: stress, sex and cognitive and emotional regulation

Abstract: The discovery of steroid hormone receptors in brain regions that mediate every aspect of brain function has broadened the definition of “neuroendocrinology” to include the reciprocal communication between the brain and the body via hormonal and neural pathways. The brain is the central organ of stress and adaptation to stress because it perceives and determines what is threatening, as well as the behavioral and physiological responses to the stressor. The adult and developing brain possess remarkable structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
159
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 169 publications
3
159
1
6
Order By: Relevance
“…As expected from previous work (24), 21-d CRS, which leads to dendritic remodeling in the CA3 hippocampus (6), resulted in a significant increase in adrenal-to-body weight ratio compared with nonstressed mice (Fig. S1) that is consistent with elevated glucocorticoid production contributing to dendritic remodeling (13). Interestingly, 21-d CRS significantly decreased the transcription of the putative presynaptic mGlu2 receptor (Fig.…”
Section: Differential Responses Of the Hippocampus To Novel And Familiarsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected from previous work (24), 21-d CRS, which leads to dendritic remodeling in the CA3 hippocampus (6), resulted in a significant increase in adrenal-to-body weight ratio compared with nonstressed mice (Fig. S1) that is consistent with elevated glucocorticoid production contributing to dendritic remodeling (13). Interestingly, 21-d CRS significantly decreased the transcription of the putative presynaptic mGlu2 receptor (Fig.…”
Section: Differential Responses Of the Hippocampus To Novel And Familiarsupporting
confidence: 89%
“…However, there are underlying changes that can be seen at the level of gene expression and epigenetic regulation that indicate that the brain is continually changing (9, 10). Epigenetic modifications, such as acetylation of histones, have also been involved in the consolidation of contextual memories that allow the brain to respond and adapt to changes in the environment (11).Among the large number of mediators of brain structural and functional plasticity, the glutamatergic system and BDNF play a key role in mediating the effects of stress on both cognition and psychopathology (1,(12)(13)(14)(15). Animal models have shown that chronic stress effects on dendritic remodeling are blocked by blocking NMDA receptors (1,16) and that adrenalectomy attenuates the acute stress-induced elevations of extracellular glutamate levels in the hippocampus (1, 17).…”
mentioning
confidence: 99%
“…Enhanced ACTH and corticosterone responses to stress in rats are known to result from increased CRF and/or AVP levels in the hypothalamus and possibly by impaired negative-feedback control by GR, MR and CRFR1 receptors in the limbic areas and by the POMC-derived peptide β-endorphin in the hypothalamus that functions to terminate stress responses (McEwen et al, 2015;Sarkar and Zhang, 2013). In addition, anxiety-related behavior is regulated by Crfr1 in the amygdala (Gilpin et al, 2015) and NPY in the hypothalamus and limbic areas (Sotnikov et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Отметим, что проблема реализации предрасполо-женности к развитию патологии ЦНС требует особого внимания в случаях, когда в исследование включают проблему формирования реакции оси гипоталамус-гипофиз-надпочечниками (т. е. реакции на стрессор, [37]. Это важно для решения актуальных проблем неврологии и психиатрии, а моделирование этих фено-менов на животных, в особенности в связи проблемой воспроизведения симптомов тревожных расстройств [49], весьма актуально.…”
Section: перепелкина ов тарасова аю полетаева ииunclassified